Sumoylation inhibits α-synuclein aggregation and toxicity - Krumova, Petranka; Meulmeester, Erik; Garrido, Manuel; Tirard, Marilyn; Hsiao, He-Hsuan; Bossis, Guillaume; Urlaub, Henning; Zweckstetter, Markus; Kügler, Sebastian; Melchior, Frauke; Bähr, Mathias; Weishaupt, Jochen H. (The journal of cell biology, 2011)
Posttranslational modification of proteins by attachment of small ubiquitin-related modifier (SUMO) contributes to numerous cellular phenomena. Sumoylation sometimes creates and abolishes binding interfaces, but increasing evidence points to another role for sumoylation in promoting the solubility of aggregation-prone proteins. Using purified α-synuclein, an aggregation-prone protein implicated in Parkinson’s disease that was previously reported to be sumoylated upon overexpression, we compared the aggregation kinetics of unmodified and modified α-synuclein. Whereas unmodified α-synuclein formed fibrils, modified α-synuclein remained soluble. The presence of as little as 10% sumoylated α-synuclein was sufficient to delay aggregation significantly in vitro. We mapped SUMO acceptor sites in α-synuclein and showed that simultaneous mutation of lysines 96 and 102 to arginine significantly impaired α-synuclein sumoylation in vitro and in cells. Importantly, this double mutant showed increased propensity for aggregation and cytotoxicity in a cell-based assay and increased cytotoxicity in dopaminergic neurons of the substantia nigra in vivo. These findings strongly support the model that sumoylation promotes protein solubility and suggest that defects in sumoylation may contribute to aggregation-induced diseases.
Gesehen am 29.07.2021